Garlic Extract-Mediated Synthesis of ZnS Nanoparticles: Structural, Optical, Antibacterial, and Hemolysis Studies. (12th February 2023) - Alnehia, Adnan; Al-Odayni, Abdel-Basit; Al-Hammadi, A. H.; Alramadhan, Safiah A.; Alnahari, Hisham; Saeed, Waseem Sharaf; Al-Sharabi, Annas
Abstract : The green synthesis of zinc sulfide nanoparticles (ZnS NPs)-mediated plant extract is gaining importance because of its simplicity, cost-effectiveness, and ecofriendly nature. In this work, ZnS NPs were synthesized using garlic extract as NPs facilitating agent, characterized by Fourier transform infrared, X-ray diffraction, scanning electron microscope, and UV–visible, then their antibacterial and hemocompatibility were assayed. Analysis revealed a cubic phase, 2.33 nm crystallite size, and a 3.75 eV optical bandgap. Bioactivity test against Staphylococcus aureus and Escherichia coli indicated dose-dependent potency closer to that of azithromycin standard drug and more efficient on S. aureus (Gram-positive) than E. coli (Gram-negative) bacteria. Biocompatibility test in terms of erythrocyte hemolysis, in reference to normal saline and water as minimal and maximal controls, confirmed nontoxic substance up to 100  μ g/mL as the highest examined concentration and at which a lysis of 2.9% was detected. Therefore, it could be concluded that this biogenic method is effective in producing ZnS NPs with desirable properties for potential biomedical applications.